Epidemiology of SARS-CoV-2 among healthcare workers in North-Eastern Italy from March 1, 2020 to May 10, 2020: COVID-19 screening in health care workers - Piapan, Linda; Mazzolini, Elena; Tomietto, Marco; Barbone, Fabio; Larese Filon, Francesca (La Medicina del Lavoro, 2021)
Background: During major epidemic outbreaks, the preparedness of public health systems is challenged and healthcare workers (HCWs) are at the frontline. Italy was among the first- and worst-hit countries by COVID-19. Aim: To analyze the prevalence and incidence of infection among HCWs in Friuli Venezia Giulia region (north-eastern Italy) from March 1 to the end of the Italian lock-down, May 10, 2020. Methods. HCWs exposed to COVID-19 patients were actively surveyed and all HCWs were routinely tested with nasopharyngeal and oropharyngeal swab for RNA virus detection (n. 54,670). Results: Infected HCWs (n. 595) represented the 32.3% of all COVID-19 cases in the region under 65 years of age, and incidence of infection was 11.4 cases/1000 workers. HCWs accounted for a significant proportion of coronavirus infection and experienced high infection incidence after unprotected contact. Conclusions. HCWs’ knowledge of SARS-CoV-2 epidemiology and proper infection control practices are critical to the control of the disease.